Evaluation of Fluoride release from orthodontic acrylic resin by using two different polymerizations techniques: An InVitro Study - Diyar B. Sabir; Zana Q. Omer (Erbil Dental Journal)
Background and objectives: Oral hygiene is mandatory for patients with orthodontic appliances and prevention of microbial biofilms in the oral environment. One method for inhibiting the growth of micro-organisms is commonly by use fluoridated dental material. The aim of this study was to evaluate releasing fluoride after addition into the orthodontic acrylic resin with 40% hydroxyethyl methacrylate, and amount of fluoride release from the orthodontic acrylic resin that was polymerized by Auto polymerization and IVOMAT polymerization.